3D Localization of FRB 20190425A for Its Potential Host Galaxy and Implications - Da-Chun Qiang; Zhi-Qiang You; Sheng Yang; Zong-Hong Zhu; Ting-Wan Chen (The Astrophysical Journal)
Fast radio bursts (FRBs) are high-energy, short-duration phenomena in radio astronomy. Identifying their host galaxies can provide insights into their mysterious origins. In this paper, we introduce a novel approach to identifying potential host galaxies in three-dimensional space. We use FRB 20190425A and GW190425 as examples to illustrate our method. Recently, due to spatial and temporal proximity, the potential association of GW190425 with FRB 20190425A has drawn attention, leading to the identification of a likely host galaxy, UGC 10667, albeit without confirmed kilonova emissions. We search for the host galaxy of FRB 20190425A with a full CHIME localization map. Regardless of the validity of the association between GW190425 and FRB 20190425A, we identify an additional potential host galaxy (SDSS J171046.84+212732.9) from the updated GLADE galaxy catalog, supplementing the importance of exploring the new volume. We employed various methodologies to determine the most probable host galaxy of GW190424 and FRB 20190425A, including a comparison of galaxy properties and constraints on their reported observation limits using various kilonova models. Our analysis suggests that current observations do not definitively identify the true host galaxy. Additionally, the kilonova models characterized by a gradual approach to their peak are contradicted by the observational upper limits of both galaxies. Although the absence of optical emission detection raises doubts, it does not definitively disprove the connection between the gravitational wave (GW) and FRB.